Ethical behaviors of tourism service providers and their impact on attracting tourists ) Sample of human resources at Baron Hotel ( Review article - Dheyaa Radhi Kadhim Alsafi (Peerian Journals Publishing, 2024)
These behaviors are innate in humans, and are therefore mentioned in the Holy Quran. Which is considered a practical, systematic and scientific constitution, on which man depends in his social life. Therefore, ethical behaviors do not only exist in one part of life, but rather exist in every aspect of a person’s life. Including the practical and scientific journey, which contains qualities that a person possesses, especially a tourist in the tourism sector. It is also one of the important topics in tourist hotels, which are described according to the services provided in them and according to the international and local standards of the tourism sector. It has many different types and practices, including: Honesty, Justice and respect, Integrity means honesty. Just as there are fixed practical behaviors in human classification, There are positive laws that govern these behaviors. In order to develop and advance the tourism sector, ethical behaviors have a significant role and impact in achieving tourist satisfaction. Which is reflected in his attraction to these tourist sites, as the tourist receives the services that meet his requirements. If he finds it of high quality in good treatment and polite behavior, he will visit those destinations, which affects the The subject of ethics in tourism organizations is one of the most difficult . increase in numbers or not administrative behaviors . The survival or continuity and growth of these organizations is largely related to environmental change and the focus on the human element. Therefore, human resources and their behavior in the environment of the tourism organization always need to be developed and improved to maintain the degree of competition between global tourism organizations. The behavior of tourism service providers is considered a basic social psychology and interacts with individual behaviors and produces positive or negative interaction, and is completely reflected in the tourism organization
Keywords: completely; interaction; organizations; tourism